BEST PRACTICE: IMPLEMENTASI PROGRAM PENDIDIKAN KEWIRAUSAHAAN MELALUI PENERAPAN PROSES PEMBELAJARAN DALAM MEWUJUDKAN KREATIVITAS DAN INOVASI PESERTA DIDIK SMA NEGERI 2 PEKANBARU TAHUN 2017: Implementation of Entrepreneurship Education Program through the Implementation of the Learning Process in Realizing Creativity and Innovation of Participants in SMA Negeri 2 Pekanbaru Academic Year 2017 - Zurina Zurina (UIR Press, 2019)
The purpose of this article was to find out whether Entrepreneurship Education Program may create an active creativity and inovation of students at SMA Negeri 2 Pekanbaru. The Entrepreneurship Education Program is one of the answers to overcome various problems, especially the problem of unemployment in Indonesia. Students need to be given debriefing on entrepreneurial competencies with the aim of preparing students in order to create jobs, alleviate the problem of unemployment, poverty, economic downturn and politically can lift the dignity and dignity as an independent nation. With the development of entrepreneurship programs the writer as the principal is more proactive in finding and utilizing opportunities to achieve success so that it will bring change in the organization towards a more adaptive one in the face of various environmental changes and 21st century challenges.Kata Kunci: Implementation, Entrepreneurship Education Program, Realizing Creativity and Innovation